Air-stable superparamagnetic metal nanoparticles entrapped in graphene oxide matrix - Tuček, Jiří; Sofer, Zdeněk; Bouša, Daniel; Pumera, Martin; Holá, Kateřina; Malá, Aneta; Poláková, Kateřina; Havrdová, Markéta; Čépe, Klára; Tomanec, Ondřej; Zbořil, Radek (Nature communications, 2016)
Superparamagnetism is a phenomenon caused by quantum effects in magnetic nanomaterials. Zero-valent metals with diameters below 5 nm have been suggested as superior alternatives to superparamagnetic metal oxides, having greater superspin magnitudes and lower levels of magnetic disorder. However, synthesis of such nanometals has been hindered by their chemical instability. Here we present a method for preparing air-stable superparamagnetic iron nanoparticles trapped between thermally reduced graphene oxide nanosheets and exhibiting ring-like or core-shell morphologies depending on iron concentration. Importantly, these hybrids show superparamagnetism at room temperature and retain it even at 5 K. The corrected saturation magnetization of 185 Am(2) kg(-1) is among the highest values reported for iron-based superparamagnets. The synthetic concept is generalized exploiting functional groups of graphene oxide to stabilize and entrap cobalt, nickel and gold nanoparticles, potentially opening doors for targeted delivery, magnetic separation and imaging applications.